2018
DOI: 10.1051/0004-6361/201833492
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding X-ray emission from the stellar radio pulsar CU Virginis

Abstract: Context. Among the intermediate mass, magnetic chemically peculiar (MCP) stars, CU Vir is one of the most intriguing objects. Its 100 % circularly polarized beams of radio emission sweep the Earth as the star rotates, thus making this strongly magnetic star the prototype of a class of non degenerate stellar radio pulsars. While CU Vir is well studied in radio, its high-energy properties are not known. Yet, X-ray emission is expected from stellar magnetospheres and confined stellar winds. Aims. Using X-ray data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The presence of non thermal X-ray photons is not a unique prerogative of the early B magnetic stars. The cooler star CU Vir (T eff ≈ 13 kK) also has an X-ray spectrum compatible with the presence of a non-thermal component (Robrade et al 2018).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The presence of non thermal X-ray photons is not a unique prerogative of the early B magnetic stars. The cooler star CU Vir (T eff ≈ 13 kK) also has an X-ray spectrum compatible with the presence of a non-thermal component (Robrade et al 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Stellar ARE from early-type magnetic stars was detected as wide band strongly circularly polarized radio pulses arising from auroral rings above the magnetic poles (Trigilio et al 2011). While the auroral signature in the UV spectrum of the prototypical star CU Vir was not found (Krtička et al 2019), the search in X-rays gives promising results (Robrade et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, radio studies of strongly magnetic chemically peculiar Bp stars revealed a variable polarimetric behavior and radio continua consistent with nonthermal processes resulting from auroral mechanisms (e.g., Leto et al 2017Leto et al , 2018Leto et al , 2020. Robrade et al (2018) suggested that the auroral mechanisms also operate in strongly magnetic Ap stars, such as CU Vir, which is detected in X-rays with L X ≈ 3 × 10 28 erg s −1 and has hard X-ray emissions with T X ≈ 25 K.…”
Section: Introductionmentioning
confidence: 89%
“…Recent improvements in the MCWS models account for the auroral emission, and are capable of explaining jointly radio and X-ray observations of magnetic B2Vp stars (Leto et al 2017(Leto et al , 2020). The auroral model was also successfully applied to the Ap star CU Vir (Robrade et al 2018). However, there are principal differences between CU Vir and KQ Vel.…”
Section: Auroral X-ray Emission Of a Magnetic Ap Starmentioning
confidence: 99%
“…Magnetic Ap/Bp stars are also X-ray emitters via magnetically confined wind shocks (MCWS; Babel & Montmerle 1997) and their magnetosphere might even generate nonthermal X-rays via auroral emission (Leto et al 2017). An application of this model to the A0p star CU Vir is presented in Robrade et al (2018) and while its spectral X-ray characteristics are comparable to those of HD 94660, its X-ray luminosity is about two orders of magnitudes lower. Although the magnetospheres of the two stars differ due to the higher magnetic field and the slower rotation of HD 94660, log L X > 30 is above what is typically observed for comparable stars.…”
Section: X-ray Emissionmentioning
confidence: 99%